Decolorization of metanil yellow dye by free and immobilized bacterial cells - Muliadi, Fatin Natasha Amira (2021)
Textile industry is one of the leading industries that contribute to economy. The oldest man-made chemicals and are widely used in the textile industries are a type of azo dyes. Globally, 2.8×105 tonnes of textile dyes are poured into water ecosystem every year. This has several adverse effects on life including decreased aquatic photosynthesis, ability to exhaust dissolved oxygen and toxic effect on flora, fauna and also humans. The presence of dyes in the textile effluent also causes an unpleasant appearance by imparting the color and also their breakdown products (colorless amines) which are toxic, carcinogenic and mutagenic. One of the examples of azo dyes is Metanil Yellow (MY) dye. MY is a type of azo dyes that is toxic to humans and also environment. Thus, this study is conducted with aims to overcome these problems. For the first objective, which is to isolate, screen and identify MY dye decolorizer from mixed culture and optimization of MY dye decolorization using RSM. The mixed bacterial culture, FN3 was isolated from agriculture soil in palm estate in Universiti Putra Malaysia, (2.9876,101.7234). Forty samples were screened for dye decolorization. The screening process was performed using different dye concentration ranging from 100 mg/L to 400 mg/L. The mixed culture was prepared by dissolving 5.0 mL of the soil suspension (10% v/v) in 50.0 mL of minimal salt medium (MSM) supplemented with desired concentration of MY dye in 250 mL conical flask. The conical flask was incubated at room temperature on a rotary shaker at 120 rpm for 24 hours. The cultures were maintained by subculturing into new MSM media every 3 days and were kept in 8°C. It was later determined that isolate FN3 able to decolorize MY up to 90% of MY dye in 24 hours. Mixed bacterial culture FN3 was then identified using metagenomics analysis. This analysis determined that the mixed bacterial culture FN3 comprised of Bacillus sp with percentage of up to 42.6%. The second highest of bacteria found in the mixed culture was from genus Acinetobacter with percentage of 14%. Fungi diversity analysis was also performed using Internal Transcribed Sequence (ITS). It was determined that 97% of mixed culture FN3 was “unclassified” fungi and 3% consisted of Candida sp. After that, the optimization of MY decolorization was performed using the methodological approach of Response Surface Methodology (RSM). From the optimization, it was determined that the optimum conditions were 72 mg/L of Metanil Yellow dye concentration, 1.934% of glucose concentration, 0.433 g/L of ammonium sulphate and pH of 7.097. The analysis of variance (ANOVA) demonstrated that the model was significant based on the low probability value (F<0.0001). The goodness of fit of the model was checked using the determination coefficient R2. The value of R2 was 0.9125 that indicated good relation between experimental and predicted values of response. The nonsignificant value of lack of fit (>0.05) shown that the quadratic model was statistically significant for the response and thus can be used for further analysis. Next, for the second objective which is to optimize the MY dye decolorization of immobilized mixed culture FN3 using RSM and to study the effects of heavy metals ions towards MY dye decolorization. The mixed bacterial culture of FN3 was immobilized using gellan gum and optimized using the same approach, RSM for optimum dye decolorization. It was determined that the optimum conditions were as follows; 130 mg/L of dye concentration, 1.478% of gellan gum concentration, 50 beads and 0.6 cm of beads size. The ANOVA test demonstrated that the model was significant for dye decolorization (F<0.0001). The value of R2 was 0.9767 which is close to 1 indicating that the correlation between the predicted and experimental values are good. The lack of fit for the model was 5.8 and statistically insignificant implying that the model was statistically significant for the response and can be used for further analysis. The reusability of the microbials beads in dye decolorizing was tested. It is documented that the immobilized beads was able to be reused up to 15 times without substantial loss of catalytic activity. The effects of metals ions were also tested to the free cells and immobilized beads of mixed bacterial culture FN3. It was shown that dye decolorization of MY by the mixed bacterial culture was not affected by the presence of 1 mg/L of the metals ions of argentum, lead, cobalt, copper, zinc, cadmium, chromium, arsenic, nickel and mercury. The ability of the immobilized beads has made this as a great potential of bioremediation tools.